Encyclopedia of animals - Howard, Jules; Vogel, Jerome (Minneapolis, MN : Wide Eyed Editions, 2019)
Presents information about three hundred species of animals, divided into such categories as invertebrates, reptiles, fish, birds, amphibians, and mammals.
Includes index.
Keywords: Animals -- Encyclopedias, Juvenile; Animals -- Encyclopedias